A Study on Determination of Seismic Susceptibility in Existing Buildings in Ward No-18 of Dhaka North Using Rapid Visual Screening (RVS) Method - Faria Islam Suijy; Anwar Hossain; Md. Mohiuddin Ahmed (International Journal of Climate Conditions, 2024)
The research work presents a comprehensive analysis of the Rapid Visual Screening (RVS) method applied to 200 buildings in Ward No. 18 of Dhaka North City. The study focused on assessing the seismic vulnerability of these structures, categorizing them into damage grades based on the RVS evaluation. Strikingly, the findings revealed that 191 out of the 200 buildings were classified as damage grade 5, signifying severe structural deficiencies. In contrast, only 9 buildings were identified with a lesser degree of vulnerability in grade 3. Furthermore, the research categorized the buildings based on their construction characteristics, distinguishing between pre-code and post-code structures. The majority, comprising 181 buildings, belonged to the pre-code category, while 19 were post-code constructions. The structural types were further delineated, with one concrete moment-resisting building, 120 concrete shear buildings, and 79 concrete frame buildings with unreinforced masonry infill walls. The alarming outcome of the study indicates a critical situation, with approximately 94.5% of the assessed buildings found to be in a vulnerable condition. This highlights the urgent need for seismic retrofitting and structural reinforcement measures in the examined area to mitigate the potential risks posed by earthquakes. The research contributes valuable insights for urban planners, policymakers, and stakeholders, emphasizing the imperative for proactive strategies to enhance the seismic resilience of structures in Dhaka North City's Ward No. 18.
Keywords: Building Vulnerability; Damage Grade; FEMA-154; Rapid Visual Screening; Vulnerability Assessment